2023
DOI: 10.1002/edn3.400
|View full text |Cite
|
Sign up to set email alerts
|

Archived DNA reveals marine heatwave‐associated shifts in fish assemblages

Abstract: Marine heatwaves can drive large‐scale shifts in marine ecosystems, but studying their impacts on whole species assemblages is difficult. Analysis combining microscopic observations with environmental DNA (eDNA) metabarcoding of the ethanol preservative of an ichthyoplankton biorepository spanning a 23 years time series captures major and sometimes unexpected changes to fish assemblages in the California Current Large Marine Ecosystem during and after the 2014–2016 Pacific Marine Heatwave. Joint modeling effor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 108 publications
0
3
0
Order By: Relevance
“…Those approaches require additional/modified sequencing protocols, which further studies should consider adopting. Our findings highlight the need to adopt protocol adaptations [110,[114][115][116][117] that facilitate quantitative comparisons of sequence proportions with biomass.…”
Section: Sequence Read Proportion Relationships and Potential Biasesmentioning
confidence: 94%
See 2 more Smart Citations
“…Those approaches require additional/modified sequencing protocols, which further studies should consider adopting. Our findings highlight the need to adopt protocol adaptations [110,[114][115][116][117] that facilitate quantitative comparisons of sequence proportions with biomass.…”
Section: Sequence Read Proportion Relationships and Potential Biasesmentioning
confidence: 94%
“…Multiple factors can lead to differences between true biomass estimates and read count data, including those prior to amplification (e.g., mt copy number, DNA extraction efficiency, sampling stochasticity, sample preservation) and others that influence the PCR reaction itself (e.g., PCR biases resulting from primer mismatch, inhibition, and other non-primer-mismatch sources leading to differences in amplification efficiency) [109][110][111][112][113][114][115][116]. For example, a meta-analysis by Piñol et al (2015) [113] found that primer mismatches accounted for 75% of amplification variation in studies.…”
Section: Sequence Read Proportion Relationships and Potential Biasesmentioning
confidence: 99%
See 1 more Smart Citation